MEDIA AUGMENTED REALITY BERBASIS DEEP LEARNING DALAM MATERI KEKAYAAN SUKU BANGSAKU: TINJAUAN PUSTAKA - Salsabila, Sabrina Putri; Awiria; Sani Aryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of Deep Learning-based Augmented Reality learning media on learning outcomes in the material of My Tribe's Wealth based on the findings of previous researchers, namely obtained from how much improvement in student learning outcomes after using Augmented Reality learning media. This study uses a literature study method by collecting 20 journals from DOAJ, Sinta, Index Copernicus, Google Scholar that are relevant and then used as a literature review, identification is done by reading, analyzing, categorizing, classifying and describing. The results of the study obtained from the analysis of the data found indicate that student learning outcomes have increased significantly after the application of Deep Learning-based Augmented Reality media. This can be seen from several opinions that support that Augmented Reality Media has an effect on improving student learning outcomes. So it can be concluded that Augmented Reality learning media can improve the learning outcomes of Elementary School students.